Humanitarian aid and political aims in Eastern Ukraine: Russian involvement and European response - Andrei SCRINIC (Eastern Journal of European Studies, 2014)
Recent events in Ukraine revealed several humanitarian issues against the background of strong pressures from Russian Federation, in its attempt to block Ukraine’s accession to the European Union (EU). This article examines how the UE, as a normative force, responds to the humanitarian crisis in Eastern Ukraine and to Russian moves to support the separatist forces, under the guise of humanitarian aid. The Russian convoys that reached the Donbas region have repeatedly breached international legislation in the humanitarian field, as documented by both Ukrainian authorities and international missions in the disputed regions. Moscow’s “humanitarian” vision appears to be a part of a wider attempt to impose the Eurasian project in its near abroad, alongside information war and outright military support for anti-government forces.